The 41BB-agonist potentiates the therapeutic efficacy of a combined irreversible electroporation ablation treatment of lung cancer by promoting unexpected CD8+CD103+ cDC1 and tissue-resident memory T cell responses - Fang, Chen; Wu, Zhaojia; Leary, Scot C.; Bai, Yiling; Yu, Michelle; Baniak, Nicolas; Ahmed, Shahid; Groot, Gary; Moser, Michael; Zhang, Wenjun; Zhang, Bing; Huang, Junqiong; et al. (Frontiers in Immunology, 2025)
Irreversible electroporation (IRE) is a relatively new, non-thermal ablation technology for cancer treatment that requires further investigation to optimize its therapeutic efficacy. To improve IRE-ablation, we developed an IRE+Combo-treatment regimen that included the Combo adjuvants poly-I:C (pIC)/CpG, anti-PD-L1 antibody (PD-L1-Ab) and the 41BB-agonist, and investigated its anti-tumor immunity in a 3LLOVA lung cancer model. We demonstrated that inclusion of the 41BB-agonist in the IRE+Combo-ablation stimulated a more efficient CD8+ T cell response (5.3%) than that observed in the absence of 41BB-agonist (3.0%) or upon IRE ablation alone (0.4%), leading to eradication of subcutaneous 3LLOVA cancer in 75% of 3LLOVA-bearing mice. We further showed that the IRE+Combo-treatment regimen resulted in the eradication of both 3LLOVA cancer and lung tumor metastases. Interestingly, our flow cytometry analyses argued that addition of the 41BB-agonist to the IRE+Combo-ablation stimulated a higher frequency of novel CD8+CD103+ conventional type-1 dendritic cells (cDC1) (14.4%) in tumor-drainage lymph-nodes (TDLNs) relative to control IRE+CpG/pIC/PD-L1-Ab- (7.5%) and IRE- (4.0%) treatment groups. This novel cDC1 subpopulation exhibited the most robust expression of DC maturation markers and costimulatory 41BBL and 41BB of all cDC1 subsets. The 41BB-agonist also stimulated a higher frequency of 41BB+CD103+TCF-1+ tissue-resident memory T (TRM) cells (14.5%) in TDLNs when compared with the two control (2.6% and 0.3%) treatment groups. Importantly, the IRE+Combo-treatment regimen was more efficient than the two control groups at converting the immunosuppressive tumor microenvironment (TME), an effect that was mitigated by reducing the frequency of inhibitory myeloid-derived suppressive cells while increasing that of immunogenic cDC1 and CD8+ T cells and rescuing T cell exhaustion. Taken together, our data establish that the 41BB-agonist potentiates the efficacy of IRE+Combo-therapy for lung cancer treatment by promoting unexpected cDC1 and TRM cell responses, and emphasize the importance of targeting this promising molecular signal to improve current cancer IRE-ablation protocols.